Balloon-based drug coating delivery to the artery wall is dictated by coating micro-morphology and angioplasty pressure gradients. (November 2020) - Tzafriri, Abraham R.; Muraj, Benny; Garcia-Polite, Fernando; Salazar-Martín, Antonio G.; Markham, Peter; Zani, Brett; Spognardi, Anna; Albaghdadi, Mazen; Alston, Steve; Edelman, Elazer R.
Abstract: Paclitaxel coated balloon catheters (PCB) were developed as a polymer-free non-implantable alternative to drug eluting stents, delivering similar drug payloads in a matter of minutes. While PCB have shown efficacy in treating peripheral arterial disease in certain patient groups, restenosis rates remain high and there is no class effect. To help further optimize these devices, we developed a scanning electron microscopy (SEM) imaging technique and computational modeling approach that provide insights into the coating micromorphology dependence of in vivo drug transfer and retention. PCBs coated with amorphous/flaky or microneedle coatings were inflated for 60 sec in porcine femoral arteries. Animals were euthanized at 0.5, 24 and 72 h and treated arteries processed for SEM to image endoluminal coating distribution followed by paclitaxel quantification by mass spectrometry (MS). Endoluminal surfaces exhibited sparse coating patches at 0.5 h, predominantly protruding (13.71 vs 0.59%, P < 0.001), with similar micro-morphologies to nominal PCB surfaces. Microneedle coating covered a 1.5-fold endoluminal area (16.1 vs 10.7%, P = 0.0035) owing to higher proximal and distal delivery, and achieved 1.5-fold tissue concentrations by MS (1933 vs 1298 μg/g, P = 0.1745) compared to amorphous/flaky coating. Acute longitudinal coating distribution tracked computationally predicted microindentation pressure gradients (r = 0.9, P < 0.001), with superior transfer of the microneedle coatings attributed to their amplification of angioplasty contact pressures. By 24 h, paclitaxel concentration and coated tissue areas both declined by >93% even as nonprotruding coating levels were stable between 0.5 and 72 h, and 2.7-fold higher for microneedle vs flaky coating (0.64 vs 0.24%, P = 0.0195). Tissue retained paclitaxel concentrations at 24–72 h trended 1.7-fold higher post treatment with microneedle coating compared to the amorphous/flaky coating (69.9 vs 39.9 μg/g, P = 0.066). Thus, balloon based drug delivery is critically dependent on coating micromorphologies, with superior performance exhibited by micromorphologies that amplify angioplasty pressures. Graphical abstract: Image 1